Problem-based seminar strategies at higher educational establishments. Novel approach - BERMICHEVA, Olena; BURUKOVSKA, Nataliia (Journal of Education, Technology and Computer Science, 2013)
The article analyses teaching technique strategies of a problem-based seminar as a methodological basis for acquisition of theoretical and practical skills by students.